Achieving the Millennium Development Goals in Sub-Saharan Africa : A Macroeconomic Monitoring Framework - Agénor, Pierre-Richard; Bayraktar, Nihal; Pinto Moreira, Emmanuel; El Aynaoui, Karim (World Bank, Washington, DC, 2012)
The authors present an integrated macroeconomic approach to monitoring progress toward achieving the Millennium Development Goals (MDGs) in Sub-Saharan Africa. At the heart of their approach is a macroeconomic model that captures key linkages between foreign aid, public investment (disaggregated into education, infrastructure, and health), the supply side, and poverty. The model is linked through cross-section regressions to indicators of malnutrition, infant mortality, life expectancy, and access to safe water. A composite MDG indicator is also calculated. The functioning of the framework is illustrated by simulating the impact of an increase in aid and a debt write-off for Niger at the MDG horizon of 2015, under alternative assumptions about the degree of efficiency of public investment. The authors' approach can serve as the building block of Strategy Papers for Human Development (SPAHD), a more encompassing concept than the current "Poverty Reduction" Strategy Papers.